2013
DOI: 10.1074/jbc.m112.413872
|View full text |Cite
|
Sign up to set email alerts
|

BBA70 of Borrelia burgdorferi Is a Novel Plasminogen-binding Protein

Abstract: Background: Recruitment of plasminogen is important for efficient dissemination of Borrelia burgdorferi. Results: BBA70 of B. burgdorferi binds plasminogen, and following activation, bound plasmin can cleave fibrinogen and inactivate the key complement components C3b and C5. Conclusion: BBA70 is a potent plasminogen-binding protein.Significance: Investigation suggests that binding of plasminogen may aid in pathogen dissemination and inhibit bacteriolytic effects of the host complement system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 90 publications
7
60
0
Order By: Relevance
“…It was previously shown that plasminogen bound at the surface of cells of the respiratory pathogen H. influenzae degrades C3b (27). In parallel, Borrelia burgdorferi recruits plasminogen and inactivates C3b as well as C5 to escape the innate immune system (25). Similar to those findings, we observed that M. catarrhalis with plasmin at the bacterial surface also degrades C3b and C5, which most likely contributes to increased resistance against serum-mediated killing.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It was previously shown that plasminogen bound at the surface of cells of the respiratory pathogen H. influenzae degrades C3b (27). In parallel, Borrelia burgdorferi recruits plasminogen and inactivates C3b as well as C5 to escape the innate immune system (25). Similar to those findings, we observed that M. catarrhalis with plasmin at the bacterial surface also degrades C3b and C5, which most likely contributes to increased resistance against serum-mediated killing.…”
Section: Discussionsupporting
confidence: 78%
“…Another approach used by microbes to degrade the ECM is to attract the zymogen plasminogen. It has been reported that when plasminogen is bound to pathogens, it contributes to adherence to host tissues (29), degradation of ECM proteins resulting in increased invasion (30), and, finally, degradation of complement (25). Interestingly, our present results also suggest that M. catarrhalis utilizes host plasminogen to escape from the innate host defense.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Plasminogen not only binds complement proteins such as C3 and C5, but has also been shown to cleave C3b and C5 upon activation to active plasmin (40). Interestingly, many pathogenic microorganisms acquire these inhibitors (including but not limited to C4BP and plasminogen) to establish an infection and evade the constant attack of complement (27,29,(41)(42)(43)(44).…”
Section: C4bp-plasminogen Interactionmentioning
confidence: 99%